Estudo e projeto de conversor cc-cc com elo de alta frequência aplicado a máquina de soldagem a arco elétrico - Rodrigo Cesar Salum Machado (2015)
This work developes a bibliography review over different isolated DC-DC static converter power topologies suitable to application of arc welding machines. Possibilities of high switching frequency of SiC in hard switching mode are explored linked by magnetics planar technology. The objective is demonstrate new possibilities of the main features desired in power electronics segment that are high power density, size reduction, efficiency, cost reduction with this technology. In this direction, was realized a project of multi-process arc welding machine of 3.9kW power and 150A/26V currente capacity in 200 kHz working switching frequency. Experimental results in rated power and over load are demonstrated.